ADHD in girls and women: a call to action – reflections on Hinshaw et al. (2021) - Chronis‐Tuscano, Andrea (Journal of child psychology and psychiatry, 2022)
This is a commentary on Hinshaw, Nguyen, O’Grady & Rosenthal’s ‘ADHD in Girls and Women: Underrepresentation, Longitudinal Processes, and Key Directions’, which reviews the empirical literature on female‐specific impairments, mechanisms and developmental pathways. Having conducted one of the most prominent and informative longitudinal investigations of girls with and without ADHD, Hinshaw et al. (2021) provide a compelling synthesis of their findings, highlighting research and clinical priorities. In this commentary, I highlight the pernicious effects of unrecognized and untreated ADHD in girls and women, challenges of making an accurate differential diagnosis and the need to raise awareness among health professionals, educators and parents about the clinical presentation of girls with ADHD in order to achieve earlier identification and intervention that can interrupt the developmental trajectory to widespread impairment, comorbidity and, in some cases, devastating outcomes.